Corticotropin-Releasing Factor (CRF) circuit modulation of cognition and motivation. (August 2019) - Hupalo, Sofiya; Bryce, Courtney A.; Bangasser, Debra A.; Berridge, Craig W.; Valentino, Rita J.; Floresco, Stan B.
Highlights: Differing levels of CRF modulate distinct forms of cognitive flexibility CRF acts in the medial septum to impair spatial memory Females are less sensitive to CRF in basal forebrain-dependent processes but are highly vulnerable to CRF actions in the LC Local CRF release in the dorsomedial PFC impairs working memory CRF activity in the VTA and NAc core regulates cost/benefit decision-making Abstract: The neuropeptide, corticotropin-releasing factor (CRF), is a key modulator of physiological, endocrine, and behavioral responses during stress. Dysfunction of the CRF system has been observed in stress-related affective disorders including post-traumatic stress disorder, depression, and anxiety. Beyond affective symptoms, these disorders are also characterized by impaired cognition, for which current pharmacological treatments are lacking. Thus, there is a need for pro-cognitive treatments to improve quality of life for individuals suffering from mental illness. In this review, we highlight research demonstrating that CRF elicits potent modulatory effects on higher-order cognition via actions within the prefrontal cortex and subcortical monoaminergic and cholinergic systems. Additionally, we identify questions for future preclinical research on this topic, such as the need to investigate sex differences in the cognitive and microcircuit actions of CRF, and whether CRF may represent a pharmacological target to treat cognitive dysfunction. Addressing these questions will provide new insight into pathophysiology underlying cognitive dysfunction and may lead to improved treatments for neuropsychiatric disorders.